If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 8k = 6k + -26 Reorder the terms: 8k = -26 + 6k Solving 8k = -26 + 6k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6k' to each side of the equation. 8k + -6k = -26 + 6k + -6k Combine like terms: 8k + -6k = 2k 2k = -26 + 6k + -6k Combine like terms: 6k + -6k = 0 2k = -26 + 0 2k = -26 Divide each side by '2'. k = -13 Simplifying k = -13

| 4x+8=-76-8x | | 3y=19+5 | | -111-7x=9x+17 | | A+(a+2)(a+2+3)=55 | | 4(5x-1)+3(1-7x)=x | | -3.2+z=-7.4 | | 5x^2-8x-4=0 | | 7(3-2x)-2(8-5x)=x | | a^2-9a+14=0 | | 5x^2+5x=0 | | X+8=3x+6 | | -21=-.6t | | Y^2-6y-7=0 | | 4x^3=64x | | p-20=-11 | | x+.12=-.25 | | c^2-9c+14=0 | | life= | | 7x-6=4x+5 | | -1.1(x+3)=5.5 | | 1.6x=.2666 | | 11+x=-6 | | .333y=.2 | | 4n-12=28 | | 1.333=.666z | | 11x+6-4=10x-2 | | 3(x+2)=8(x-1)+5 | | 2.6q-3.4-5.1q=-3.5q-5.6 | | 58+12x= | | p+2p-3=6 | | 77z=693 | | -3(x-4)-4x=-4(x+2)-5x | | -4(3b+1)+(13b-4)=0 | | 5c+3-4C=-30+9 | | 6-3(3x-2)=-33 | | lx+5l=9 | | 5p=-35 | | 6(x+4)=3(2x+4)+12 | | 3-2k=-7 | | 2(3x-3)-22(x+1)=15 | | -9.3x=27.9 | | 8x-17=7x-17 | | 9x-7=9(x+9) | | 96x=2208 | | 2x-1=11x-82 | | 5+12x=82+x | | 6x+8=-83-7x | | 5x^3-24x^2+x+12=0 | | taco=fart | | 35=7 | | 6x^2+24x+16=142 | | 2m-1=-6m+5 | | -35-7x=10x+16 | | 4(x-1)=7x-19 | | 6s+13s=133 | | -7-2x=13-7x | | 14-8x=44-29x | | -3x+8=32 | | 1000(x-4)(x-7)=0 | | 8x+2+6x+8=13x+5 | | 5p+6=-4p-08 | | 14-x=20 | | 9+18x-2=9x+46-4x | | 72-5x=4x+24 | | 26+8x-18=0 |